Molecular engineering of branched polymers through 1, 1-diphenyl-ethylene chemistry and anionic polymerization. (April 2015) - Hong, Linxiang; Yang, Shaohui; He, Junpo
Graphical abstract: Highlights: An anionic inimer approach was developed for the synthesis of star-branched polymers. Hyperbranched polymers were synthesized through self-condensing vinyl copolymerization of the anionic inimer. Dendrimer-like polymers with orthogonal functionalities were synthesized in a fast, divergent, and living procedure. Ultra high molecular weight dendrimer-like polymers were synthesized. Cylindrical polymer brushes with high density of side chains were prepared. Abstract: In this feature article, we describe the synthetic work in our laboratory on branched polymers through anionic polymerization reaction based on selective addition of organolithium toward a bifunctional 1, 1-diphenylethylene derivative, 1, 3-bis(1-phenylvinyl)benzene (MDDPE). Exclusive monoaddition was achieved using equal molar ratio of organolithium and MDDPE in THF, in which the solvent polarity played a decisive role for the addition behavior. The monoaddition was used in the synthesis of ABC- and ABCD-type miktoarm star polymers through successive reactions on the double bonds of MDDPE. The monoadduct, either with butyllithium or polymeric lithium, was also utilized as inimer or macroinimer to synthesize hyperbranched polymers, hyperbranched block copolymers or terpolymers, respectively, through self-condensing vinyl copolymerization (SCVCP) with vinyl monomer. A very specific application of the anionic inimer is the development of a continuous process for the synthesis of living dendrimer-like polymers. By this approach, dendrimer-like polystyrene of 5th generation can be synthesized within 12 h. Functionalization and copolymerization were also possible on the basis of living dendrimer-like polymers. We also developed another facile method for the synthesis dendrimer-like polymers using anionic "grafting-to" reaction. Dendritic products with extremely large molecular weights were obtained. In addition, the anionic "grafting-to" reaction was used in the synthesis of graft polymers with "V-shaped", "Y-shaped", "comb-on-comb" and dendritic side chains.